PENGARUH RETRIBUSI OBJEK WISATA, JUMLAH WISATAWAN, PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KARANGANYAR - Sri Indriyani, Suprihatmi Sri Wardiningsih & Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This study aims to analyze the retribution of tourist attractions, the number of tourists and entertainment taxes to the original income of karanganyar regency. This study uses quantitative data and uses secondary data sources. The population of this research is 48 data and sample of this research consist of 48 data from retribution of tourist object, number of tourists, entertainment tax and local revenue. Data analysis techniques use classical assumption test, multiple linear regression, t test, F test and coefficient of determination. The result of research partially indicate that the retribution of tourist object and the number of tourist tourists have positive but not significant effect to the original income of the region. The entertainment tax has a positive and significant effect on the local revenue. Simultaneously the retribution of tourist attraction, the number of tourists and entertainment tax has a positive and significant effect on the local revenue.Keywords: local revenue, levy of tourist attraction, number of tourists, entertainment tax